EAGLE-FLI. A macroeconomic model of banking and financial interdependence in the euro area - Nikola Bokan; Andrea Gerali; Sandra Gomes; Pascal Jacquinot; Massimiliano Pisani (European Central Bank (ECB), 2016)
We incorporate financial linkages in EAGLE, a New Keynesian multi-country dynamic general equilibrium model of the euro area (EA) by including financial frictions and country-specific banking sectors. In this new version of the model, termed EAGLE-FLI (Euro Area and GLobal Economy with Financial LInkages), banks collect deposits from domestic households and cross- country interbank market and raise capital to finance loans issued to domestic households and firms. In order to borrow from local (regional) banks, households use domestic real estate as collateral whereas firms use both domestic real estate and physical capital. These features – together with the full characterization of trade balance and real exchange rate dynamics and with a rich array of financial shocks – allow to properly assess domestic and cross-country macroeconomic effects of financial shocks. Our results support the views that (1) the business cycles in the EA can be driven not only by real shocks, but also by financial shocks, (2) the financial sector can amplify the transmission of (real) shocks, and (3) the financial/banking shocks and the banking sectors can be sources of business cycle asymmetries and spillovers across countries in a monetary union.
Keywords: E51; E32; E44; F45; F47; 330; banks; DSGE models; econometric models; financial frictions; open-economy macroeconomics; policy analysis